Automated detection of glaucoma using optical coherence tomography angiogram images. (December 2019) - Chan, Yam Meng; Ng, E.Y.K.; Jahmunah, V.; Wei Koh, Joel En; Lih, Oh Shu; Wei Leon, Leonard Yip; Acharya, U. Rajendra
Abstract: Glaucoma is a malady that occurs due to the buildup of fluid pressure in the inner eye. Detection of glaucoma at an early stage is crucial as by 2040, 111.8 million people are expected to be afflicted with glaucoma globally. Feature extraction methods prove to be promising in the diagnosis of glaucoma. In this study, we have used optical coherence tomography angiogram (OCTA) images for automated glaucoma detection. Ocular sinister (OS) from the left eye while ocular dexter (OD) were obtained from right eye of subjects. We have used OS macular, OS disc, OD macular and OD disc images. In this work, local phase quantization (LPQ) technique was applied to extract the features. Information fusion and principal component analysis (PCA) are used to combine and reduce the features. Our method achieved the highest accuracy of 94.3% using LPQ coupled with PCA for right eye optic disc images with AdaBoost classifier. The proposed technique can aid clinicians in glaucoma detection at an early stage. The developed model is ready to be tested with more images before deploying for clinical application. Highlights: Automated detection of glaucoma using OCTA images. OS macular, OS disc, OD macular and OD disc images are considered. LPQ, Information fusion, PCA, and AdaBoost classifier are used. Obtained accuracy of 94.3% for OD optic disc images.